The Analysis of Attitude and Consumer Preferences to Purchase Decisions of Banana Fruit in Traditional Markets Pangkalpinang City - Aprilia Damayanti; Eni Karsiningsih; Muntoro Muntoro (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study examines consumer perceptions of the qualities considered in purchasing decisions and consumer preferences for purchasing bananas in traditional markets in Pangkalpinang. This research was carried out in a predetermined traditional market in Pangkalpinang City. This study used a survey method as its primary research design. Purposive sampling was used, and the sample size was 100 respondents. The attributes of bananas analyzed were tasted, fruit skin color, fruit size, and number of fruit per comb. The analytical method used is Fishbein Multiattribute analysis and Conjoint analysis. The results showed that consumer attitudes toward the attributes that were most considered in purchasing bananas were attributes of fruit skin color (21.57) which was very positive—taste (16.27), which was a positive value. Fruit size (15, 87) is a positive value, and the number of fruit per comb (6,41) is negative. Consumer preferences in purchasing bananas at the traditional Pangkalpinang City market are bananas with a yellow-green skin color, a sweet banana taste, a length of > 14 cm, and many pieces per comb with> 16 details. The sequence of importance values explains the attributes of bananas that the consumer pays the most attention to when buying bananas: the color of the banana peel, the taste of the banana, the size of the banana, and the number of bananas per comb.